The board chair effect across countries: An institutional view - Krause, Ryan; Li, Weiwen; Ma, Xufei; Bruton, Garry D. (Strategic Management Journal, 2019)
Abstract Research Summary Strategic leadership scholars have produced consistent evidence that the CEO effect on firm performance depends on the latitude of actions CEOs enjoy in their particular context. We argue that as the governance leaders of their firms, board chairs choose a firm's objectives more than they do its actions. As a result, the board chair effect should vary with latitude of objectives, rather than latitude of actions. We explore this possibility by comparing the board chair effect in two countries with relatively high latitude of objectives—Germany and China—with the board chair effect in two countries with relatively low latitude of objectives—the United States and United Kingdom. Results confirm that latitude of objectives influences the effect of board chair heterogeneity on firm performance. Managerial Summary Do board chairs matter to different degrees in different countries? Building on prior work showing that U.S. board chairs account for a significant portion of firm performance, we collected data on board chairs from four different countries to find out if this effect differs by institutional environment. We find that board chairs matter for firm performance across countries, but that board chairs in Germany and China exhibit a considerably larger effect on firm performance than do board chairs in the United States and United Kingdom. We interpret these findings as evidence that board chairs enjoy wider discretion with regard to organizational objectives in Germany and China than they do in the United States and United Kingdom.